Extracellular vesicles in idiopathic pulmonary fibrosis: pathogenesis and therapeutics - Yu Fujita (BMC, 2022)
Abstract Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease that occurs due to increased fibrosis of lung tissue in response to chronic injury of the epithelium. Therapeutic options for IPF remain limited as current therapies only function to decrease disease progression. Recently, extracellular vesicles (EVs), including exosomes and microvesicles, have been recognized as paracrine communicators through the component cargo. The population of cell-specific microRNAs and proteins present in EVs can regulate gene expressions of recipient cells, resulting in modulation of biological activities. EV cargoes reflect cell types and their physiological and pathological status of donor cells. Many current researches have highlighted the functions of EVs on the epithelial phenotype and fibroproliferative response in the pathogenesis of IPF. Furthermore, some native EVs could be used as a cell-free therapeutic approach for IPF as vehicles for drug delivery, given their intrinsic biocompatibility and specific target activity. EV-based therapies have been proposed as a new potential alternative to cell-based approaches. The advantage is that EVs, depending on their source, may be less immunogenic than their parental cells, likely due to a lower abundance of transmembrane proteins such as major histocompatibility complex (MHC) proteins on the surface. In the last decade, mesenchymal stem cell (MSC)-derived EVs have been rapidly developed as therapeutic products ready for clinical trials against various diseases. Considering EV functional complexity and heterogeneity, there is an urgent need to establish refined systemic standards for manufacturing processes and regulatory requirements of these medicines. This review highlights the EV-mediated cellular crosstalk involved in IPF pathogenesis and discusses the potential for EV-based therapeutics as a novel treatment modality for IPF.